Trends in HIV Prevalence, Condom Use and Associated Factors among Female Sex Workers in Denpasar, Bali, Indonesia - Dewa Nyoman Wirawan; Emily Rowe; Made Suarjaya; Luh Putu Sri Armini (Public Health and Preventive Medicine Archive, 2014)
Objectives: The purpose of this paper is to review trends of HIV prevalence, condom use and associated risk factors among the female sex workers (FSW) in Denpasar, Bali. Methods: To analyze trends of HIV prevalence, surveillance data from 2000-2013 was used. Survey data from 2007 to 2013 was referenced for analysis of condom use trends. Data on associated risk factors was taken from 2012 integrated HIV and behavior survey. Results and conclusion: HIV prevalence among direct FSW in 2000 was as low as 1.6% (95%CI: 0.05-3.15) and continued to rise, reaching a prevalence peak of 22.5% (95%CI: 16.4-26.6) in 2010. HIV prevalence began to decline in 2011, 2012 and 2013. Analysis unearthed similar prevalence trends among indirect FSW albeit with a much lower prevalence of 0.25% in 2001, rising to 7.2% in 2010 and declining to 2.2% in 2013. The proportion of direct FSW reporting to always wear condoms in the last working week increased from 38% in 2007 (95%CI: 33.3-42.7) to 65% in 2013 (95%CI: 60.4-69.6). Multivariate analysis with logistic regression indicated that the significant risk factor with HIV prevalence was the specific grouping of FSW, in that low/mid-price are more at risk in comparison to high price with OR=4.37 (95%CI: 1.42-13.38). Risk factors associated with condom use was also the specific group of FSW, high price reported higher condom use with OR=4.04 (95%CI:2.03-8.04) and greater role of sex work site ‘pimps’ in encouraging their FSW to reject clients refusing to wear condoms with OR=2.06 (95%CI: 1.29-3.30). HIV prevalence among indirect and high-price direct FSW was much lower compared to prevalence in low/mid-price direct FSW. HIV prevalence and condom use among direct FSW population are significantly associated with group price range and the role of ‘pimps’.